GM-CSF-neuroantigen fusion proteins reverse experimental autoimmune encephalomyelitis and mediate tolerogenic activity in adjuvant-primed environments: association with inflammation-dependent, inhibitory antigen presentation() - Islam, S.M. Touhidul (2014)
Single-chain fusion proteins comprised of GM-CSF and neuroantigen (NAg) are potent, NAg-specific inhibitors of experimental autoimmune encephalomyelitis (EAE). An important question was whether GMCSF-NAg tolerogenic vaccines retained inhibitory activity within inflammatory environments or were contingent upon steady-state conditions. A GMCSF-MOG fusion protein reversed established paralytic disease in both passive and active models of EAE in C57BL/6 mice. The fusion protein also reversed EAE in CD4-deficient and B cell-deficient mice. Notably, GMCSF-MOG inhibited EAE when co-injected adjacent to the MOG35-55/CFA emulsion. GMCSF-MOG also retained dominant inhibitory activity when directly emulsified with MOG35-55 in the CFA emulsion in both C57BL/6 or B cell-deficient models of EAE. Likewise, when combined with PLP139-151 in CFA, GMCSF-PLP inhibited EAE in SJL mice. When deliberately emulsified in CFA with the NAg, GMCSF-NAg inhibited EAE even though NAg was present at more than a 30-fold molar excess. In vitro studies revealed that the GMCSF domain of GMCSF-MOG stimulated growth and differentiation of inflammatory dendritic cells (DC) and simultaneously targeted the MOG35-55 domain for enhanced presentation by these DC. These inflammatory DC presented MOG35-55 to MOG-specific T cells by an inhibitory mechanism that was mediated in part by IFN-γ signaling and NO production. In conclusion, GMCSF-NAg was tolerogenic in CFA-primed pro-inflammatory environments by a mechanism associated with targeted antigen presentation by inflammatory DC and an inhibitory IFN-γ/ NO pathway. The inhibitory activity of GMCSF-NAg in CFA-primed lymphatics distinguishes GMCSF-NAg fusion proteins as a unique class of inflammation-dependent tolerogens that are mechanistically distinct from naked peptide or protein-based tolerogens.